Disruption and overexpression of 6-phosphofructo-2-kinase influence organic acid production in Aspergillus carbonarius ITEM 5010 - Yang, Lei; Nilsson, Lena; Lübeck, Mette; Ahring, Birgitte K.; Bruno, Kenneth S.; Lübeck, Peter S. (World journal of microbiology & biotechnology, 2020)
Aspergillus carbonarius is an efficient producer of organic acids with great potential for bio-based production of organic acids. In this study, we identified a gene f2kp encoding the enzyme 6-phosphofructo-2-kinase known as an allosteric regulator of the glycolytic flux and investigated its role in the production of organic acid. The strategy was to examine the impact of citric acid and malic acid production by overexpressing and disrupting f2kp , respectively. The overexpressing transformants expressed f2kp at higher level than the wild type, whereas no expression of f2kp was detected in the knockout transformants. Citric acid and malic acid production by the knockout strains decreased sharply along with a significant lower sugar consumption, though the overexpressing transformants produced similar amounts of citric acid and malic acid as the wild type. We conclude that 6-phosphofructo-2-kinase has an important regulatory role for the glycolytic flux and organic acid production in A. carbonarius.